2020
DOI: 10.1097/corr.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of the COVID-19 Pandemic on Quality of Life and Other Patient-reported Outcomes? An Analysis of the Hand-Wrist Study Cohort

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic, and its associated lockdowns in many parts of the world, have changed our daily lives and may have a psychological impact on around the globe. However, it is unknown how this influences the patient-reported outcome measures (PROMs) of patients involved in ongoing clinical research and medical care. For both the current and potential future lockdowns, it is important to determine if PROMs collected during such a period can be interpreted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The damage caused by the COVID pandemic in different aspects of health care and infection control has been devastating, although not yet sufficiently analyzed [16][17][18][19][20] . At the beginning of the pandemic, it was already anticipated that patients with severe COVID-19 would develop superinfections, most commonly pneumonia due to nosocomial bacteria and invasive aspergillosis 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The damage caused by the COVID pandemic in different aspects of health care and infection control has been devastating, although not yet sufficiently analyzed [16][17][18][19][20] . At the beginning of the pandemic, it was already anticipated that patients with severe COVID-19 would develop superinfections, most commonly pneumonia due to nosocomial bacteria and invasive aspergillosis 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…An impaired quality of life has been also reported in literature during COVID-19 pandemic due to the social distancing [13,14]. Moreover, related lockdown measures could impact on mental health, due to isolation [15,16]. In addition to concerns associated with the diffusion of the outbreak, limited access to hospital facilities during the quarantine period could make patients with chronic disorders susceptible to psychological stress.…”
Section: Of 13mentioning
confidence: 92%
“…15 The EQ-5D-5L has been validated in hundreds of countries and languages, providing a standardized approach to measure and compare health within and across nations. 15 Since the pandemic began, the EQ-5D-5L has been used to assess HRQoL in the Netherlands, 18 Germany, 19 France, 20 Morocco, 21 China, 22 Hong Kong, 23 Vietnam, 24 and Spain 25 in various contexts including the general public, those with speci c diseases, and healthcare providers; these studies have shown an overall decline in HRQoL, and pronounced worsening of anxiety and depression. The objective of this study was to assess the impact of COVID-19 on US population health using the EQ-5D-5L.…”
Section: Introductionmentioning
confidence: 99%